Valves selecting to close algorithm in water distribution system using flow analysis - Antonowicz, Ariel; Leszek, Mateusz; Urbaniak, Andrzej; Zakrzewski, Przemysław (Instal, 2024)
The article proposes the use of simulation tools to minimize the total number of valves needed to isolate a selected segment of a water supply network based on flow analysis. Based on the hydraulic model, valve location information and simulation results, the proposed solution indicates which valves should be closed so that no flow occurs in the analyzed pipe. The implemented algorithm, in addition to indicating the identifiers of the valves necessary to completely isolate a given section, informs whether it is possible to reduce the number of these valves, and if so, indicates which valves do not need to be closed (and in what time interval). The results of the simulation, together with the proposal of groups of valves to be closed, are saved directly to the indicated CSV file. The correctness of the developed and implemented method was verified on the example of an unreal water distribution system.
Keywords: EPANET; WNTR; hydraulic simulations; selecting valves for closure